The Effectiveness Of The Baznas Program Of Banyuwangi Regency In Improving Community Welfare - Vina Wafiatul Fauziah; Faiqotul Himmah; Wiwit Mustafidah (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study aims to evaluate the effectiveness of BAZNAS Banyuwangi's programs in enhancing beneficiary welfare across five dimensions: economic, educational, social, health, and religious. A descriptive qualitative method was employed, with data collected through participatory observation, in-depth interviews, and documentation. The results identify five core programs: Banyuwangi Makmur, Cerdas, Peduli, Sehat, and Taqwa. Overall, all programs positively impact beneficiaries, with varying effectiveness levels. The Banyuwangi Makmur (Prosperous) program proved most effective by focusing on economic empowerment through business capital and tools, demonstrably increasing income and fostering long-term self-reliance, thereby creating sustainable economic change. Other programs contributed significantly: Cerdas (Intelligent) alleviated educational costs, Peduli (Caring) improved living standards through social aid, Sehat (Healthy) enhanced healthcare access, and Taqwa (Pious) strengthened spiritual facilities. In conclusion, BAZNAS Banyuwangi's zakat distribution strategy is effective. However, program sustainability and impact could be optimized through improved mentoring and more equitable program distribution. Keywords : BAZNAS, effectiveness programe, community welfare